Improvement of the Level of Learners or “Abusive Results”?: A Survey of Gabon’s Fourth-Year Primary School Teachers on the CBA Correction Grids - Pambou, Jean-Aimé; Eny, Jean Jacques Essono (Journal of Organizational Psychology, 2021)
In the context of frequent debates on the Competency-Based Approach in Gabon, we focused on primary school teachers, who are required to use this approach in their classrooms. Based on qualitative and quantitative approach, this work presents the results of a questionnaire on the use of rubrics for correcting written production in Grade 4. Essentially, almost all of the nineteen informants (18/19) acknowledged that the proposed rubrics now help in the practice of remediation activities, but several (15/19) also argued that they tend to promote "abusive results" in the evaluation of learners' writing. Inspired by both cognitivist and socio-constructivist theories, our contribution allows us to identify certain grievances against the CBA in Gabon and to formulate proposals to ensure that the problems of written production are better taken into account.